Analysis of The Legality of The Online Forex Business in The Perspective of Sharia Economics and Finance - Nursaman, Nursaman; Ikhsanudin, Ikhsanudin (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2026)
The rapid development of information technology has significantly transformed the financial sector, particularly in digital-based investment activities such as online forex trading. This study aims to analyze the legality of online forex transactions from the perspective of Islamic economics and finance. Employing a qualitative approach through a literature review, the study is structured into five main areas: online forex trading in Islamic economics and finance, its legality in conventional systems and national regulations, its legal status from an Islamic perspective, development solutions, and the opportunities and challenges involved. Online forex trading refers to the exchange of currencies conducted digitally without physical delivery, typically within futures markets. From the standpoint of Islamic economics and finance, such practices raise critical concerns regarding compliance with Sharia principles, particularly due to the potential presence of riba (usury), gharar (uncertainty), and maisir (speculation). These elements are often embedded in high-risk and speculative trading mechanisms, which contradict the core values of justice, transparency, and permissibility (halal).Therefore, while online forex trading may be legally recognized in conventional financial systems, its Sharia compliance remains questionable. Strengthening regulatory frameworks aligned with Islamic principles, enhancing public literacy in Islamic finance, and developing Sharia-compliant trading platforms are essential steps. Continuous supervision and innovation are also necessary to ensure that such financial activities are not only legally valid but also ethically and religiously acceptable.